Labor enforcement and formal employment: The effects of communication and punishment - Miguel Nathan Foguel; Carlos Henrique Corseuil (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
We evaluate the effects of a large-scale enforcement intervention on formal labor flows. The initiative combined a communication component (an official letter/e-mail sent to registered employers) and a punishment component (face-to-face inspections). Using two identification strategies (regression discontinuity design - RDD and difference-in-differences - DiD) we isolate the effects of each component keeping the other constant. Results show that both components increased the formalization of previous informal workers but did not change regular, formal labor demand. Effects are observed only for the short run, indicating that employers reacted to each component in the aftermath of the intervention and then moved back to their usual compliance behavior.
Keywords: J88; J46; H83; 330; enforcement intervention; labor inspection; formal employment